2019
DOI: 10.18502/ijpa.v14i2.1139
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Vivo Scolicidal Activities of Holothuria leuco-spilota Extract and CeO2 Nanoparticles against Hydatid Cyst

Abstract: Background: We aimed to investigate the scolicidal effects of Holothuria leucospilota extract and CeO2 nanoparticles against protoscoleces of hydatid cysts in-vitro and in-vivo. Methods: Hydatid cysts were collected from, Urmia slaughterhouses between years 2016-2017 and the hydatid fluid aspirated from the fertile cysts. Various concentration of H. leucospilota extract, CeO2 NPs and combination of CeO2-NPs/H. leucospilota were used for 10-60 min to evaluate the viability of protoscoleces by 0.1% eosin m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In vitro results showed that the most protoscolicidal effects were reported for extract (70% at 20 mg/mL for 60 min), followed by the combination of this extract and Ce nanoparticles (63% in 15 mg/mL concentration for 1 h). Furthermore, in vivo assay demonstrated that all three compounds significantly reduced the number and size of the hydatid cysts compared to the control group that received no treatment [ 30 ] . …”
Section: Discussionmentioning
confidence: 99%
“…In vitro results showed that the most protoscolicidal effects were reported for extract (70% at 20 mg/mL for 60 min), followed by the combination of this extract and Ce nanoparticles (63% in 15 mg/mL concentration for 1 h). Furthermore, in vivo assay demonstrated that all three compounds significantly reduced the number and size of the hydatid cysts compared to the control group that received no treatment [ 30 ] . …”
Section: Discussionmentioning
confidence: 99%
“…Moazeni et al [ 14 ] tested the therapeutic effects of Z. multiflora nanoemulsion in vivo and revealed a reduction in hydatid cyst burden. In another study, cerium oxide nanoparticles showed a decreased mean weight and size of hydatid cysts in treated mice [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have investigated the benefits of this nanoparticle, such as antimicrobial, anti-cancer, treatment, and antioxidant activities [71,72]. In a study by Aryamand et al (2019), the in vitro and in vivo protoscolicidal effects of Holothuria leucospilota extract alone, CeO2 nanoparticles alone, and extract combined with CeO2 NPs were investigated for 10 to 60 min. In vitro results showed that the most protoscolicidal effects were reported for extract (70% at 20 mg/mL for 60 min), followed by the combination of this extract and Ce nanoparticles (63% in 15 mg/mL concentration for 1 h).…”
Section: Cerium Dioxide Nanoparticlesmentioning
confidence: 99%